EVALUATION OF GROWTH AND NUTRIENT DIGESTIBILITY OF LABEO BATA FED WITH PLANT MATTER INCORPORATED DIETS - ANJANA, MS; DAS, S. K. (Journal of the Inland Fisheries Society of India, 2021)
Six iso-nitrogenous and iso-caloric experimental diets were formulated by partial replacement of fishmeal with leaf powders of Eichhornia crassipes and Colocasia esculenta at different levels.These diets were evaluated with fish meal based control diet for growth performance and nutrient digestibility in fingerlings of Labeo bata. Growth of fish and nutrient digestibility of feed was not significantly different in experimental diets partially replaced fish meal at 20% and 30% level compared to control diet and thus reduced the feed cost. However, growth and digestibility was adversely affected at 40% level of substitution of fish meal with leaf powder in the diets. Key Words : Fish meal, replacement, weed, digestibility, L. bata.